EVALUASI PENGGUNAAN OBAT PADA PASIEN HIPERTENSI RAWAT JALAN DI RUMAH SAKIT UMUM WISMA RINI PRINGSEWU TAHUN 2019 - Ramadhan Triyadi; Akhmad Rokiban; Anggun Carima (Fakultas MIPA Universitas Tulang Bawang Lampung, 2020)
Abstract Hypertension is a non-communicable disease characterized by the increase of systolic blood pressure is >140 mmHg and diastolic blood pressure is >90 mmHg. Hypertension is also the major risk factor of other cardiovascular disease. The incidence rate of hypertension with or without complications increases every year, so the potential for inaccurate use of drugs is increasing. The purpose of this research is to determine the characteristics of hypertension outpatients and the proper hypertension drug use in hypertension outpatients at Wisma Rini General Hospital Pringsewu in 2019 based on the proper patient, the proper indication, the proper drug, and the proper dose using the standard reference of Guidelines JNC VIII. This research is descriptive research, the data was collected retrospectively based on medical records. The sample collection technique in this research is using a purposive sampling technique. The results in this study obtained from 110 patient samples diagnosed with the hypertension showed that most of hypertension patients are women (55,46%), mostly aged 56-65 years old (40%), and the most taken hypertension drug is CCB group amlodipine with 78 patients (71%). The evaluation of antihypertensive drug use obtained is proper patient with 110 patients (100%), proper indication with 110 patients (100%), proper drug with 92 patients (75,6%), and proper dose with 110 patients (100%). Keywords: Antihypertensive, Hypertension, Accuracy drug use.